Involvement of the TGF-β pathway in epithelial-mesenchymal transition promoted by the pulmonary microenvironment in Mycoplasma pneumoniae pneumonia - Fan, Lu; Wang, Huixia; Xu, Nuo; Guo, Yun; li, Ling (Archives of Biological Sciences, 2024)
Paper description: Mycoplasma pneumoniae pneumonia (MPP) can lead to atelectasis and even pulmonary fibrosis, the rationale for which is unclear. Transcriptome sequencing, immunohistochemistry, Western blotting, immunofluorescence, and ELISA were used to assess whether the pulmonary microenvironment in MPP patients with atelectasis induces epithelial-mesenchymal transition (EMT), and to investigate the signaling pathways involved. The TGF-β, p53, Hippo, and Rap1 pathways were upregulated; the differentially expressed genes were enriched in the TGF-β signaling pathway. EMT induced by BALF from MPP patients with atelectasis is closely related to the TGF-β signaling pathway, which may be one of the mechanisms leading to long-term pulmonary fibrosis. Abstract: Mycoplasma pneumoniae (MP), one of the smallest prokaryotic microorganisms capable of independent survival, causes respiratory tract infections and various extrapulmonary diseases. Mycoplasma pneumoniae pneumonia (MPP) is the most significant clinical manifestation, often leading to complications such as atelectasis and pulmonary fibrosis. We explored the role of the pulmonary microenvironment in regulating epithelial-mesenchymal transition (EMT) in MPP patients with atelectasis. Transcriptome sequencing revealed significant upregulation of pathways including transforming growth factor beta (TGF-β), tumor protein 53 (P53), protein kinase Hippo, Ras-proximate-1 or Ras-related protein 1 (Rap1), and members of class O forkhead box proteins (FoxO) in cells exposed to bronchoalveolar lavage fluid (BALF) from MPP patients with atelectasis. Among these, the TGF-β pathway exhibited the most pronounced changes in gene expression. Further analysis confirmed that BALF from these patients induced EMT in human bronchial epithelial cells and mouse lung tissues and that TGF-β receptor kinase inhibitor (TRKI) effectively reversed this process. In conclusion, the pulmonary microenvironment in MPP patients with atelectasis promotes EMT in the lungs, with TGF-β playing a key role in this process. This may represent a crucial mechanism contributing to pulmonary fibrosis, underscoring the need to focus on the pulmonary microenvironment and TGF-β-targeted therapies for the prevention and management of pulmonary fibrosis in these patients.